A method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material

By using a silicon-carbon composite material supported by carbon cloth in the negative electrode material of lithium-ion battery, the problem of poor stability caused by volume changes in silicon-based materials during circulation is solved, and the goals of high specific capacity and low cost are achieved, which significantly improves the cycling performance and stability of the battery.

CN117747760BActive Publication Date: 2025-03-18UNIV OF ELECTRONICS SCI & TECH OF CHINA +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311645464.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-04
Publication Date
2025-03-18
Estimated Expiration
2043-12-04

AI Technical Summary

Technical Problem

The volume expansion and contraction of existing silicon-based lithium-ion battery anode materials lead to poor stability during circulation, and the preparation process is complex and costly, making it difficult to achieve high specific capacity and low cost.

Method used

Using a carbon cloth-supported silicon-carbon composite material preparation method, by self-assembly and chemically bonding tetraethyl orthosilicate and long carbon chain organosilane to the surface of cotton fibers, a self-assembly monolayer with a relatively regular structure is formed, and then carbonized and activated under the protection of inert gas to form a silicon-carbon composite material, and spread and bonded on the carbon cloth to enhance conductivity and stability.

Benefits of technology

It significantly alleviates the shrinkage stress caused by volume changes in silicon during circulation, enhances cycling performance, improves the stability and specific capacity of the battery, and simplifies the process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117747760B_ABST
    Figure CN117747760B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of energy storage, and specifically is a method for preparing a silicon-carbon negative electrode material for a lithium-ion battery supported by carbon cloth. The preparation method utilizes the fact that the cellulose surface in cotton contains a large number of hydroxyls, so that organic silane can be stably grafted on the cotton surface through chemical bonding, and self-organizes to form a uniform monolayer to complete the modification of the cotton. Then the modified cotton is carbonized and activated at a temperature range of 400 to 900° C. under the protection of an inert gas to obtain a silicon-carbon composite material. Since the composite material is a composite structure with silicon particles grafted on the surface, the silicon particles grafted on the outer layer can give full play to the advantages of its high specific volume, while the carbon skeleton provides a buffer zone for volume expansion and enhances conductivity; combined with the good mechanical properties of carbon cloth, the support on the electrode surface can alleviate the volume expansion of silicon during the cycle to the maximum extent, and maintain the integrity of the electrode material. The silicon-carbon composite material prepared by the method of the present invention has the advantages of strong conductivity and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energy storage, and in particular relates to a method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material. Background Art

[0002] Lithium-ion batteries (LIBs) have attracted widespread attention due to their fast charge and discharge rates and high specific capacity, especially in the fields of portable electronic devices and electric transportation. To meet the performance requirements of lithium-ion batteries for electric vehicles, developing negative electrode materials with high power and high energy density is one of the most important issues in this field.

[0003] Silicon is an abundant and environmentally friendly material that can be extracted in large-scale, high-purity forms. It has a large lithium insertion potential and a theoretical capacity of up to 4200mAh / g, which is much higher than the theoretical capacity of graphite. This makes silicon considered one of the most promising negative electrode materials for the next generation of lithium-ion batteries, which can replace traditional carbon materials. However, there are still some problems with the application of pure silicon negative electrode materials or negative electrode materials with high silicon content in lithium-ion batteries, mainly manifested in poor conductivity, and large volume changes of materials caused by lithium ion insertion and extraction during the cycle, resulting in pulverization of active materials and poor electrode cycle stability. In order to solve these problems, many literatures have reported improved silicon materials, which have a larger tolerance range of volume changes and stronger conductivity.

[0004] The silicon-carbon composite negative electrode materials reported in the existing reports can be roughly divided into three categories: one is the structural design of silicon materials, such as silicon nanowire structure, which can provide short-path lithium ion diffusion. The second category, such as carbon coatings, metals and conductive polymers, introduces conductive materials on the silicon surface through optimization strategies to increase the conductivity of silicon materials, and uses the introduced conductive materials to buffer the volume changes of silicon. The third category is to conduct bulk phase research on silicon-based negative electrode materials, design porous three-dimensional structures, interfaces and surface structures, etc. Among them, the silicon-carbon composite material with nanowire structure has excellent electron transmission ability and more electron transmission paths, which is conducive to enhancing the conductivity and electrode activity of the electrode. At the same time, it can also reduce the expansion and contraction of the electrode material, which can improve the stability and reliability of the battery.

[0005] For example, in the Chinese patent application with publication number CN116682956A and invention name "A method for preparing a silicon nanowire @ carbon negative electrode material for lithium-ion batteries", a negative electrode material with a tubular structure of carbon-coated silicon is disclosed. Silicon tetrachloride is reduced with zinc powder by chemical vapor deposition technology to obtain silicon nanowires, and the surface of the silicon nanowires is treated with surfactant hexadecyltrimethylammonium bromide. The treated silicon nanowires are transferred to a carbon source solution to obtain a silicon-carbon composite material precursor, and high-temperature sintering is performed to obtain silicon nanowire @ carbon negative electrode material. It is used in lithium-ion batteries, showing a higher specific capacity and excellent cycle stability, with a capacity retention rate of 97% after 500 cycles. However, its preparation process is complicated, and after the thermal reduction of silicon tetrachloride with zinc metal, the metal will not exist in the final material, resulting in low atomic utilization.

[0006] For example, in the Chinese patent with publication number CN106531967A and invention name "A method for preparing a lithium battery negative electrode material of cobalt tetraoxide ferroate-carbon cloth", a lithium battery negative electrode material of cobalt tetraoxide ferroate-carbon cloth is disclosed, in which the carbon cloth is treated with ferrocyanide and cobalt salt to obtain a precursor, and the precursor is heat-treated. CoFe2O4 grows in situ on the carbon cloth, providing an electron transfer pathway between the active material and the current collector, and alleviating the huge volume expansion during the cycle. Due to the use of only carbon cloth, although the cycle stability can be improved, its specific capacity is low and the process yield is low.

[0007] Based on the above research, it can be seen that the existing silicon-based negative electrode material structure still needs to be improved in its preparation process. While solving the problems of volume expansion and poor cycle stability, how to simplify the process and achieve low cost and high specific capacity is still a problem to be solved. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material, which utilizes carbon cloth to improve ionic and electronic conductivity, effectively alleviates the volume expansion and contraction stress of silicon during the cycle, enhances the cycle performance, and has the characteristics of simple specific process and low cost.

[0009] To achieve the above object, the present invention adopts the following technical solution:

[0010] A method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material comprises the following steps:

[0011] Step 1: Wash and dry the cotton with ethanol, place it in a container, and add it to the solvent. The addition ratio is 20 to 30 ml of solvent per gram of cotton; mix tetraethyl orthosilicate and long carbon chain organosilane in a volume ratio of 1: (1 to 3) and add them to the container; add 1.2 to 2 ml of catalyst to the container, react for a period of time, and remove the solvent to obtain a precursor.

[0012] Step 2: The precursor obtained in step 1 is carbonized and activated in a temperature range of 400 to 900° C. under the protection of an inert gas to obtain a silicon-carbon composite material.

[0013] Step three: disperse the binder in a solvent to form a solution; place the silicon-carbon composite material and the conductive agent obtained in step two in a container, add an appropriate amount of binder solution and stir thoroughly; then spread it evenly on the carbon cloth, attach another carbon cloth of the same size to the surface of the active material, and dry it in a vacuum drying oven to obtain a silicon-carbon composite material; wherein the ratio of the binder to the solvent is 1g:(5-10)ml, and the mass ratio of the binder solution, the conductive agent, and the silicon-carbon composite material is 1:(1-4):(5-8).

[0014] Furthermore, the solvent in step 1 is one or a mixture of ethanol, methanol, ethyl acetate, acetone and toluene.

[0015] Furthermore, the long carbon chain organosilane in step 1 is one or a mixture of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, octyltrimethoxysilane, perfluorooctyltrimethoxysilane, octyltriethoxysilane, dodecyltriethoxysilane, hexadecyltriethoxysilane, octadecyltriethoxysilane, perfluorooctyltriethoxysilane, and 3-aminopropyltriethoxysilane.

[0016] Furthermore, the catalyst in step 1 is one of ammonia water, hydrochloric acid and sulfuric acid.

[0017] Furthermore, the inert gas in step 2 is one of nitrogen, argon and helium.

[0018] Furthermore, the carbonization activation time in step 2 is 4 to 8 hours.

[0019] Furthermore, in step 3, the conductive agent is one or a mixture of graphene, carbon nanotubes, acetylene black, Ketjen black, and conductive carbon black.

[0020] Furthermore, the binder in step three is a mixture of one or more of the following: a composite binder commonly used in lithium-ion battery negative electrode materials (polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, sodium carboxymethyl cellulose CMC, polyacrylonitrile PAN, polyvinyl alcohol PVA, polyacrylic acid PAA, styrene-butadiene rubber SBR) or other functionalized binders.

[0021] Furthermore, the solvent of the adhesive in step three is one of N-methylpyrrolidone, ethanol, acetone, diacetyl, and ethyl acetate.

[0022] Furthermore, the thickness of the carbon cloth in step three is 0.05 mm to 0.2 mm.

[0023] Furthermore, the synthesized silicon-carbon composite material is a linear structure of silicon-coated carbon. Preferably, the silicon content in the silicon-carbon composite material is 10-25wt%.

[0024] The above technical solution of the present invention has the following advantages compared with the prior art:

[0025] (1) The raw material of the present invention is cotton, which is mainly composed of cellulose and contains a large number of hydroxyl groups on the surface and is easy to be functionalized.

[0026] (2) Traditional silicon-carbon negative electrode materials are made by physically mixing silicon and carbon and adding a small amount of adhesive to stabilize the material during the cycle. However, the adhesive faces the problem of aging during long cycles and cannot withstand the volume change during the silicon lithium insertion / delithiation process, which will cause the specific capacity to be irreversibly and significantly attenuated. The present invention provides a method for preparing a carbon cloth-supported silicon-carbon composite material, wherein the carbon cloth has excellent electrochemical and mechanical properties. The support of the carbon cloth on both sides of the electrode greatly alleviates the shrinkage stress caused by the volume change of silicon during the cycle, and avoids the substantial capacity attenuation caused by the pulverization and shedding of the active material of the electrode during long cycles.

[0027] (3) In addition, the traditional silicon-carbon negative electrode material is to bond silicon particles and carbon materials with adhesives for physical mixing and bonding, while the patent of the present invention innovatively self-assembles and chemically bonds silicon particles and carbon materials on the surface at the precursor stage, greatly enhancing the interaction and stability between silicon-carbon materials. The specific mechanism is as follows: after hydrolysis, tetraethyl orthosilicate can undergo condensation reaction with hydroxyl groups on the cotton surface for grafting, and can also undergo condensation reaction with hydroxyl groups obtained after hydrolysis of long carbon chain organosilanes for grafting, so that long carbon chain organosilanes and tetraethyl orthosilicate can self-assemble on the cotton fiber surface to form a self-assembled monolayer with a relatively regular and uniform structure. In addition, the addition of long carbon chain organosilanes allows tetraethyl orthosilicate to hydrolyze and condense on the cotton fiber surface to form an orderly and controllable structure, which is conducive to the formation of chemical bonding between silicon and carbon after the next step of carbonization activation, forming a carbon-silicon-carbon structure. After carbonization and activation under inert gas, cotton fiber, hydrolyzed tetraethyl orthosilicate, and long carbon chain organosilane were dehydrogenated and deoxygenated to form a silicon-carbon composite material (C@SiO x / C). The carbon in the inner layer enhances the ion and electron transport capabilities, allowing the material to withstand high current density charging and discharging. The tight chemical bonding between silicon and the carbon in the inner layer and the carbonized long carbon chain organic silane filling alleviate the volume expansion of silicon during the cycle, greatly enhancing the cycle stability of the material.

[0028] (4) The present invention provides a method for preparing a carbon cloth-supported silicon-carbon composite material, which has a simple process, is easy to operate, has low cost, and has almost no impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 a is a schematic diagram of an embodiment of the present invention applied to a lithium-ion battery, Figure 1 b is a partial schematic diagram of an embodiment of the present invention, Figure 1 c is a schematic diagram of the structure of the silicon-carbon composite material obtained after carbonization and activation of cotton fibers.

[0030] Among them, 1. carbon cloth; 2. silicon dioxide particles (SiO x ), conductive agent, and a mixture of silicon-carbon materials. DETAILED DESCRIPTION

[0031] In order to make the above features, purposes, and advantages of the present invention more obvious and understandable, the specific implementation methods of the present invention are described in detail below. The embodiments are only to enable those skilled in the art to better understand and implement the present invention, but are not intended to limit the present invention.

[0032] Example 1

[0033] This embodiment provides a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material, and the preparation method thereof is as follows:

[0034] Step 1: Place the cotton in a beaker containing excess anhydrous ethanol, ultrasonicate it in an ultrasonic cleaner for 10 minutes, and then dry it in an oven; take 2g of the dried cotton and place it in a beaker, and add 40ml of ethanol, 0.25ml of tetraethyl orthosilicate, and 0.5ml of dodecyltrimethoxysilane, and stir it on a magnetic stirrer for 10 minutes; then, add 2ml of ammonia water dropwise into the beaker during the stirring process, and after the addition of ammonia water is completed, let it stand and react for 22 hours; after the reaction is completed, wash the cotton twice with ethanol to wash away the reactants on the cotton surface, and dry it in a vacuum drying oven to obtain a precursor.

[0035] Step 2: Carbonize and activate the precursor in a nitrogen atmosphere, set the heating rate to 5°C / min, keep it at 450°C for 2h, and then keep it at 800°C for 5h, and finally obtain a silicon-carbon composite material. Figure 1 c.

[0036] Step 3: Dissolve 3g of binder PVDF in 20ml of ethanol; mix 1g of silicon-carbon composite material with 0.2g of graphene in a container, add 1.2ml of binder solution, and stir for 20h; evenly coat the stirred slurry on a carbon cloth (10cm×5cm), and immediately cover the surface of the active material with another carbon cloth of the same size, transfer to a vacuum drying oven for drying, and obtain a carbon cloth-supported silicon-carbon composite negative electrode material. The structure of this material can be found in Figure 1 a- Figure 1 b.

[0037] Example 2

[0038] This embodiment provides a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material, and the preparation method thereof is as follows:

[0039] Step 1: Place the cotton in a beaker containing excess anhydrous ethanol, ultrasonicate it in an ultrasonic cleaner for 10 minutes, and then dry it in an oven; take 2g of the dried cotton and place it in a beaker, and add 50ml of methanol, 0.3ml of tetraethyl orthosilicate, and 0.3ml of hexadecyltrimethoxysilane, and stir it on a magnetic stirrer for 10 minutes; then, add 1.2ml of hydrochloric acid dropwise into the beaker during the stirring process, and after the addition of hydrochloric acid is completed, let it react for 18 hours; after the reaction is completed, wash the cotton twice with ethanol to wash away the reactants on the cotton surface, and dry it in a vacuum drying oven to obtain a precursor.

[0040] Step 2: Carbonize and activate the precursor in an argon atmosphere, set the heating rate to 5°C / min, keep it at 400°C for 2 hours, and then keep it at 850°C for 5 hours, and finally obtain a silicon-carbon composite material.

[0041] Step 3: Dissolve 3g of binder CMC in 25ml of ethanol; mix 1g of silicon-carbon composite material with 0.2g of carbon nanotubes in a container, add 1.0ml of binder solution, and stir for 20h; the stirred slurry is evenly coated on a carbon cloth (10cm×5cm), and immediately another carbon cloth of the same size is covered on the surface of the active material, and transferred to a vacuum drying oven for drying to obtain a carbon cloth-supported silicon-carbon composite negative electrode material.

[0042] Example 3

[0043] This embodiment provides a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material, and the preparation method thereof is as follows:

[0044] Step 1: Place the cotton in a beaker containing excess anhydrous ethanol, ultrasonicate it in an ultrasonic cleaner for 10 minutes, and then dry it in an oven; take 2g of the dried cotton and place it in a beaker, and add 45ml of methanol, 0.25ml of tetraethyl orthosilicate, and 0.4ml of octadecyltrimethoxysilane, and stir it on a magnetic stirrer for 10 minutes; then, add 2ml of sulfuric acid dropwise into the beaker during the stirring process, and after the addition of sulfuric acid is completed, let it react for 21 hours; after the reaction is completed, wash the cotton twice with ethanol to wash away the reactants on the cotton surface, and dry it in a vacuum drying oven to obtain a precursor.

[0045] Step 2: Carbonize and activate the precursor in a helium atmosphere, set the heating rate to 5°C / min, keep it at 500°C for 2 hours, and then keep it at 750°C for 5 hours, and finally obtain a silicon-carbon composite material.

[0046] Step 3: Dissolve 5g of binder CMC in 30ml of ethanol; mix 1g of silicon-carbon composite material with 0.1g of acetylene black in a container, add 0.9ml of binder solution, and stir for 15h; the stirred slurry is evenly coated on a carbon cloth (10cm×5cm), and immediately another carbon cloth of the same size is covered on the surface of the active material, and transferred to a vacuum drying oven for drying to obtain a carbon cloth-supported silicon-carbon composite negative electrode material.

[0047] Example 4

[0048] This embodiment provides a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material, and the preparation method thereof is as follows:

[0049] Step 1: Place the cotton in a beaker containing excess anhydrous ethanol, ultrasonicate it in an ultrasonic cleaner for 10 minutes, and then dry it in an oven; take 2g of the dried cotton and place it in a beaker, and add 50ml of methanol, 0.3ml of tetraethyl orthosilicate, and 0.2ml of perfluorooctyltriethoxysilane, and stir it on a magnetic stirrer for 10 minutes; then, add 1.8ml of ammonia water dropwise into the beaker during the stirring process, and after the addition of ammonia water is completed, let it stand and react for 18 hours; after the reaction is completed, wash the cotton twice with ethanol to wash away the reactants on the cotton surface, and dry it in a vacuum drying oven to obtain a precursor.

[0050] Step 2: Carbonize and activate the precursor in a nitrogen atmosphere, set the heating rate to 5°C / min, keep it at 450°C for 3 hours, and then keep it at 800°C for 5 hours to finally obtain a silicon-carbon composite material.

[0051] Step 3: Dissolve 3g of binder PAA in 30ml of ethanol; mix 1g of silicon-carbon composite material with 0.3g of Ketjen black in a container, add 1.0ml of binder solution, and stir for 20h; the stirred slurry is evenly coated on a carbon cloth (10cm×5cm), and immediately another carbon cloth of the same size is covered on the surface of the active material, and transferred to a vacuum drying oven for drying to obtain a carbon cloth-supported silicon-carbon composite negative electrode material.

[0052] Example 5

[0053] This embodiment provides a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material, and the preparation method thereof is as follows:

[0054] Step 1: Place the cotton in a beaker containing excess anhydrous ethanol, ultrasonicate it in an ultrasonic cleaner for 10 minutes, and then dry it in an oven; take 2g of the dried cotton and place it in a beaker, and add 45ml of methanol, 0.5ml of tetraethyl orthosilicate, and 0.8ml of octadecyltriethoxysilane, and stir it on a magnetic stirrer for 10 minutes; then, add 2ml of sulfuric acid dropwise into the beaker during the stirring process, and after the addition of sulfuric acid is completed, let it react for 24 hours; after the reaction is completed, wash the cotton twice with ethanol to wash away the reactants on the cotton surface, and dry it in a vacuum drying oven to obtain a precursor.

[0055] Step 2: Carbonize and activate the precursor in a nitrogen atmosphere, set the heating rate to 5°C / min, keep it at 400°C for 3 hours, and then keep it at 900°C for 5 hours, and finally obtain a silicon-carbon composite material.

[0056] Step 3: Dissolve 4g of binder SBR in 25ml of ethanol; mix 1g of silicon-carbon composite material with 0.2g of carbon nanotubes in a container, add 0.8ml of binder solution, and stir for 20h; the stirred slurry is evenly coated on a carbon cloth (10cm×5cm), and immediately another carbon cloth of the same size is covered on the surface of the active material, and transferred to a vacuum drying oven for drying to obtain a carbon cloth-supported silicon-carbon composite negative electrode material.

[0057] Comparative Example 1

[0058] In this comparative example, the prepared linear silicon-carbon composite material is subjected to the traditional lithium-ion battery preparation process, the active material, the conductive agent, and the adhesive are mixed and fully ground, and coated on the copper foil to make a button battery, and the electrochemical performance is compared with the silicon-carbon composite material supported by the carbon cloth provided by the present invention. The preparation process is as follows:

[0059] (1) Place cotton in a beaker containing excess anhydrous ethanol, ultrasonicate in an ultrasonic cleaning agent for 10 minutes, repeat this operation three times, and place the cotton in an oven to dry. Take 2g of dried cotton and place it in a beaker and put in a magnet, add 40ml of ethanol, 0.5ml of tetraethyl orthosilicate, and 0.5ml of dodecyltrimethoxysilane, and stir on a magnetic stirrer for 10 minutes. Subsequently, 2ml of ammonia water is added dropwise to the beaker during stirring, and after the addition of ammonia water is completed, the reaction is allowed to stand for 20 hours. Take out the cotton, wash it twice with ethanol, wash off the unreacted dodecyltrimethoxysilane and tetraethyl orthosilicate on the surface of the cotton, and dry it in a vacuum drying oven to obtain a precursor. The precursor is carbonized and activated in a nitrogen atmosphere, the heating rate is set to 5℃ / min, and it is kept at 450℃ for 2 hours, and then kept at 800℃ for 7 hours to obtain a silicon-carbon composite material.

[0060] (2) Preparation of negative electrode sheet:

[0061] The silicon-carbon composite material, acetylene black and PVDF were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone was added as a dispersant, and stirred for 20 hours. The stirred slurry was evenly coated on the copper foil and transferred to a vacuum drying oven for drying.

[0062] Electrochemical performance test:

[0063] Examples 1-5 were tested using soft-pack batteries, with lithium sheets as counter electrodes, Celgard 2300PP / PE / PP three-layer microporous composite membranes as diaphragms, and 1M LiPF6 mixed solution of EC, EMC, and DMC (v / v / v=1:1:1) as electrolytes. The carbon cloth-supported silicon-carbon composite material was connected to the tabs to form battery sheets, and the battery sheets and diaphragms were placed in soft-pack battery shells and packaged to ensure the safety and sealing of the battery. The electrolyte was injected into the battery shell and sealed to ensure the normal operation of the battery. All assembly processes were carried out in a dry glove box filled with argon. Comparative Example 1 was tested by making a button battery, with lithium sheets as counter electrodes, Celgard 2300PP / PE / PP three-layer microporous composite membranes as diaphragms, and 1M LiPF6 mixed solution of EC, EMC, and DMC (v / v / v=1:1:1) as electrolytes, and assembled with the negative electrode sheet in Comparative Example 1 to obtain a button battery.

[0064] The soft-pack button battery constructed as above was kept at room temperature overnight and subjected to a long cycle test using an Arbin charge and discharge tester at a current density of 0.5 A g -1 , the charge and discharge voltage is limited to 0.005-1.500 V. The initial specific capacity, capacity retention rate after 300 cycles, and coulombic efficiency after 300 cycles are shown in Table 1.

[0065] Table 1

[0066]

[0067] It can be seen from Table 1 that the silicon-carbon composite material supported by the carbon cloth prepared by the present invention has a high initial charge and discharge capacity and excellent cycle stability. When the cotton is modified, with the increase of the amount of long carbon chain organosilane and tetraethyl orthosilicate, and the increase of reaction time, the overall specific capacity of the silicon-carbon composite material is improved, but the capacity retention rate of the electrode decreases during the long cycle, and the cycle stability becomes poor. By comparing the comparative example with the embodiment, it can be seen that the support of the carbon cloth for the electrode material greatly alleviates the expansion of the active material, which not only enhances the cycle performance, but also significantly increases the specific capacity of the electrode material. Through appropriate material design, the initial discharge specific capacity of the battery can exceed 1100mAh g -1 After 300 cycles, the coulombic efficiency can still exceed 99%, indicating that the carbon cloth-supported silicon-carbon composite negative electrode material provided by the present invention has excellent electrochemical properties and is an ideal next-generation silicon-carbon negative electrode material.

Claims

1. A method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material, characterized in that: The following steps are involved: Step 1: Wash and dry cotton with ethanol, place it in a container, and add it to a solvent, with the addition ratio being 20 to 30 ml of solvent per gram of cotton; mix tetraethyl orthosilicate and long carbon chain organosilane in a volume ratio of 1:(1 to 3) and add them to the container; add 1.2 to 2 ml of a catalyst to the container, react for a period of time, and remove the solvent to obtain a precursor; the catalyst is one of ammonia water, hydrochloric acid, and sulfuric acid; Step 2: The precursor obtained in step 1 is carbonized and activated at a temperature range of 400 to 900 °C for 4 to 8 h under the protection of an inert gas to form a silicon-carbon composite material C@SiOx / C; Step 3: Disperse the binder in a solvent to form a solution; place the silicon-carbon composite material and the conductive agent obtained in step 2 in a container, add the binder solution and stir thoroughly; then spread it evenly on the carbon cloth, attach another carbon cloth of the same size to the surface of the active material, and dry it in a vacuum drying oven to obtain a silicon-carbon composite negative electrode material; wherein the ratio of the binder to the solvent is 1g:(5-10) ml, and the mass ratio of the binder solution, the conductive agent, and the silicon-carbon composite material is 1:(1-4):(5-8).

2. The method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that The solvent in step 1 is one or a mixture of ethanol, methanol, ethyl acetate, acetone and toluene.

3. The method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that The long carbon chain organosilane in step 1 is dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, octyltrimethoxysilane, perfluorooctyltrimethoxysilane, octyltriethoxysilane, One or a mixture of dodecyltriethoxysilane, hexadecyltriethoxysilane, octadecyltriethoxysilane, perfluorooctyltriethoxysilane, and 3-aminopropyltriethoxysilane.

4. The method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that : The inert gas in step 2 is argon or helium.

5. According to the method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material as claimed in claim 1, the conductive agent in step 3 is one or a mixture of graphene, carbon nanotubes, and conductive carbon black.

6. The method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that The adhesive in step 3 is one or a mixture of the following: polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, polyacrylonitrile PAN, polyvinyl alcohol PVA, polyacrylic acid PAA or styrene-butadiene rubber SBR.

7. The method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that The solvent of the adhesive in step 3 is one of N-methylpyrrolidone, ethanol, acetone, diacetyl, and ethyl acetate.

8. The method for preparing a carbon cloth-supported lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that : The thickness of the carbon cloth described in step 3 is 0.05 mm to 0.2 mm.

Citation Information

Patent Citations

  • Preparation method of cobalt diiron tetraoxide-carbon cloth lithium battery anode material

    CN106531967A

  • Preparation method of silicon nanowire-coated carbon negative electrode material for lithium battery as well as product and application of silicon nanowire-coated carbon negative electrode material

    CN116682956A

  • Silicon-coated carbon fiber nano composite material and preparation method and application thereof

    CN103730645A

  • Preparation method of micron silicon negative electrode for lithium ion batteries

    CN106684335A